Kinerja Kepolisian Resor Seruyan dalam Menangani Kasus Narkoba Jenis Pil Koplo di Kabupaten Seruyan - Irwani Irwani; Muhammad Rifa'i (Pencerah Publik, 2015)
This study aims to study and find out the performance of the police at Seruyan Resort in treating cases of pill type Koplo drugs in Seruyan district. To find out Seruyan resort police performance in handling cases of pill type Koplo drugs in Seruyan, I used five performance measurement indicators according to Dwiyanto namely productivity, service quality, responsiveness, Responsibility, and accountability. In conducting this research, I use qualitative research methods, this method is meant to describe the performance of police resort Seruyan in dealing cases drug type Koplo pills in Seruyan. In qualitative research, the problem is still temporary and will develop or change after researchers are in the field. The data source consists of the primary source (the head of the Criminal Investigation Unit, the head of the drug Reserve Unit, the community, and the suspected illegal drugs case). The technique is data-related with interviews, observations, and documentation. The results showed that Seruyan resort police performance in handling cases of pill type Koplo drugs in Seruyan district seen from the five indicators according to Dwiyanto, there are still problems faced such as information on arrest That are leaked by certain parties to distributors, distributors who flee or concealed by the family such as out of town or in the woods.